2003
DOI: 10.1093/emboj/cdg473
|View full text |Cite
|
Sign up to set email alerts
|

Differential role of p300 and CBP acetyltransferase during myogenesis: p300 acts upstream of MyoD and Myf5

Abstract: Studies in tissue culture cells have implicated p300 and CBP acetyltransferases in myogenic regulatory factor (MRF) mediated transcription and terminal differentiation of skeletal muscle cells. However, in vivo data placing p300 and CBP on myogenic differentiation pathways are not yet available. In this report we provide genetic evidence that p300 but not CBP acetyltransferase (AT) activity is required for myogenesis in the mouse and in embryonic stem (ES) cells. A fraction of embryos carrying a single p300 AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
142
1
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(154 citation statements)
references
References 61 publications
8
142
1
3
Order By: Relevance
“…Our study presents strong evidence that CBP and p300 have distinct functions in the regulation of survivin transcription. The results are consistent with recent publications suggesting nonredundant roles for CBP and p300 in cell growth, differentiation and development, in spite of their high degree of homology (Kawasaki et al, 1998;Yao et al, 1998;Kung et al, 2000;Yamauchi et al, 2002;Roth et al, 2003). Rebel et al (2002), using a hematopoietic stem cell (HSC) model, concluded that CBP but not p300 is essential for HSC self-renewal, whereas p300 is critical for proper hematopoietic differentiation.…”
Section: Discussionsupporting
confidence: 92%
“…Our study presents strong evidence that CBP and p300 have distinct functions in the regulation of survivin transcription. The results are consistent with recent publications suggesting nonredundant roles for CBP and p300 in cell growth, differentiation and development, in spite of their high degree of homology (Kawasaki et al, 1998;Yao et al, 1998;Kung et al, 2000;Yamauchi et al, 2002;Roth et al, 2003). Rebel et al (2002), using a hematopoietic stem cell (HSC) model, concluded that CBP but not p300 is essential for HSC self-renewal, whereas p300 is critical for proper hematopoietic differentiation.…”
Section: Discussionsupporting
confidence: 92%
“…Frameshift and nonsense mutations affecting the HAT domain represent the most frequent mutation types observed in RSTS with the CREBBP 1 -3,5,6 and EP300 4 genes. However, the location of the present frameshift EP300 gene mutation and RSTS N Zimmermann et al mutation very close to the 3 0 -end of EP300 is interesting; 3,5,6,11,16 it leads to a putative very mild truncation that does not alter the HAT domain, and could possibly explain the non-classical RSTS (unusual face, relatively good intelligence) in our patient. An overbite with the maxillary incisors markedly protruding over the lower lip and requiring maxillary surgery is an unusual feature in RSTS.…”
Section: Discussionmentioning
confidence: 64%
“…Since p300 HAT activity is critical for myogenic differentiation [22,23], we first used Western blot analysis to examine changes in the global levels of p300 and histone acetylation during early myoblast differentiation. As shown in Figure 1(c,d), the expression of myogenin, a specific marker of terminal differentiation, was induced (over 10-fold) by 24 hours of differentiation compared to proliferating myoblasts, but the level of p300 protein remained relatively steady.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, genetic studies in mice and embryonic stem (ES) cells have clearly shown that the intrinsic HAT activity of p300, but not CBP, is specifically required for skeletal myogenesis and MyoD gene expression [22,23]. Interestingly, depletion of MyoD in myotubes leads to a reduction of H3K27ac, particularly, where the majority of myotube-specific enhancers bound by MyoD are co-occupied with p300 [16].…”
Section: Introductionmentioning
confidence: 99%